The alienation, the meaning of concept and it’s manifestations in the Arab - Fettache, Noura (Journal of Human Sciences, 2021)
Aliénation is one of the expériences which human being go through since his birth. despite all civilization that he enjoys he become one of the most influenced by aliénation because of the fast changing of his life’s style and the unlimited power of technology that distanced him from his identity and his role as principle actor in his life. Based on this réality,our study aims to answer the following questions ?How did philosofical approches the concept of alénation ?What are the new forms of this concept in te contemporary arab society.